(untitled) (DAPesquisa, 2020)
This text is a presentation of formulations, ways and images based on the title question ’what is performative writing?’, presenting the collection of texts from the proposal From theme to ways, reflections and inventions: research in arts and research writing, produced by artist-researchers from different Brazilian universities, who bring with them the interest and reflective exercise of Research in Art in and through writing, sharing their procedures and possibilities.